PENGARUH LATIHAN DIAMOND PASSING TERHADAP KEMAMPUAN PASSING DAN CONTROL DALAM PERMAINAN FUTSAL SISWA EKSTRAKURIKULER SMK NEGERI 4 BONE - Amar Ma’ruf, Amar Ma’ruf; Andi Mutmainna, Andi Mutmainna; Alif Aryadi Hardi, Alif Aryadi Hardi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effect of diamond passing training on passing and control ability in futsal games for extracurricular students at SMK Negeri 4 Bone. This quantitative research used a one group pretest-posttest design with 15 students selected through purposive sampling. Data were analyzed using Shapiro-Wilk normality test, Levene homogeneity test, and paired samples t-test via SPSS Version 23. Results showed a significant effect of diamond passing training on passing ability (t = 10.835 > t table = 1.761; p = 0.000 < 0.05) and control ability (t = 10.983 > t table = 1.761; p = 0.000 < 0.05). Mean improvement in passing was 3.73 points (from 4.27 to 8.00) and in control was 3.93 points (from 4.47 to 8.40). Diamond passing training is proven effective in improving basic technical skills of passing and control in futsal.